Implementasi Nilai-Nilai Al-Qur’an dan Hadits Nabi Dalam Kehidupan Peserta Didik di MTS. Raudlatul Hasaniyah Mojolegi Gading Probolinggo - Mahmud Yunus; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the implementation of the values of the Qur'an and the Hadith of the Prophet in the daily lives of students at MTs. Raudlatul Hasaniyah, Mojolegi Gading Probolinggo. The primary focus of this research is to explore how the values contained in the Qur'an and Hadith are applied in students' everyday lives, particularly in the spiritual, social, and moral aspects. A qualitative approach using a case study method was employed, with data gathered through in-depth interviews, observations, and document analysis. The findings indicate that the implementation of Qur'anic and Hadith values at MTs. Raudlatul Hasaniyah is carried out effectively through various educational programs and initiatives based on Islamic teachings. These values are applied in both academic learning, extracurricular activities, and students' daily life within the school environment. The positive impacts experienced by students include improved moral character, discipline, and a deeper understanding of Islamic teachings. This research is expected to contribute to the development of Islamic education based on Qur'anic and Hadith values in shaping a generation with strong character.